Traditional use of medicinal plants among the tribal communities of Chhota Bhangal, Western Himalaya - Jamwal Pankaj; Singh KN; Uniyal Sanjay Kr; Lal Brij (BMC, 2006)
Abstract The importance of medicinal plants in traditional healthcare practices, providing clues to new areas of research and in biodiversity conservation is now well recognized. However, information on the uses for plants for medicine is lacking from many interior areas of Himalaya. Keeping this in view the present study was initiated in a tribal dominated hinterland of western Himalaya. The study aimed to look into the diversity of plant resources that are used by local people for curing various ailments. Questionnaire surveys, participatory observations and field visits were planned to illicit information on the uses of various plants. It was found that 35 plant species are commonly used by local people for curing various diseases. In most of the cases (45%) under ground part of the plant was used. New medicinal uses of Ranunculus hirtellus and Anemone rupicola are reported from this area. Similarly, preparation of "sik" a traditional recipe served as a nutritious diet to pregnant women is also not documented elsewhere. Implication of developmental activities and changing socio-economic conditions on the traditional knowledge are also discussed.